The association between the composition of the early-life intestinal microbiome and eczema in the first year of life - Leo, Stefano; Cetiner, Omer Faruk; Pittet, Laure F.; Messina, Nicole L.; Jakob, William; Falquet, Laurent; Curtis, Nigel; Zimmermann, Petra (Frontiers in Microbiomes, 2023)
Introduction The early-life intestinal microbiome plays a crucial role in the development and regulation of the immune system. Perturbations in its composition during this critical period have been linked to the development of allergic diseases. Objective This study aimed to investigate the association between the composition of the early-life intestinal microbiome and the presence of eczema in the first year of life using shotgun metagenomic sequencing and functional analyses (metabolic pathways). Methods Stool samples from 393 healthy term infants collected at 1 week of age were analyzed with shotgun metagenomic sequencing. Environmental and clinical data were prospectively collected using 3-monthly validated questionnaires. Participants were clinically assessed during study visits at 12 months of age. Eczema was diagnosed by the UK diagnostic tool and by a research nurse. Data analysis was stratified by delivery mode. Results Eczema was diagnosed in 16.4% (60/366) of participants by nurse diagnosis. Infants born by cesarean section (CS) with nurse-diagnosed eczema had a higher relative abundance of Escherichia, Shigella, Enterobacter, and Citrobacter and a lower relative abundance of Veillonella than CS-born infants without eczema. In addition, CS-born infants without eczema had a higher abundance of genes involved in lactic fermentation. Vaginally born infants with eczema had a higher relative abundance of Bacteroides and a lower abundance of Streptococcus. Conclusion There is an association between the bacterial composition of the intestinal microbiome at 1 week of age and the presence of eczema in the first 12 months of life.